Nucleate boiling heat transfer during water-IN-oil emulsion drop impact onto a heated solid surface - Ashikhmin A. E. Alexander Evgenjevich; Semyonova A. E. Aleksandra Evgenjevna; Fyodorov V. S. Vladislav Sergeevich; Misyura S. Ya. Sergey Yakovlevich; Piskunov M. V. Maksim Vladimirovich (2023, 2023)
Title screen